(untitled) (Journal of Information Technologies in Education (ITE), 2014)
The article examines the development of technologies open education. We describe the views of scientists on the concept of «open education» and functionally related terms «e-learning»,«global educational space», «information-educational environment», «technology open education» and others. Examines possibilities technologies open education for informatization of the educational process.